Induction motor macromodel based on experimental data - Matviychuk, Yaroslav (Publishing House of Lviv Polytechnic National University, 2014)
The macromodel of transients of a threephase induction motor in the terms of stator current, rotation rate and loading on the axis is described. Experimantal data are averaged per an alternating current (AC) period. Regularization of the experimantal data differentiation is demonstrated using cubic smoothing splines. The number of coefficients of macromodel is minimized by reduction of the approximating polynomial. Due to the reduction of macromodel the identification became correct. Adequate behavior of the macromodel has been verified for input signals different from those for which the macromodel has been built. Experimental transients are reproduced by two continuous nonlinear maсromodels of the first order with a relative mean square error less than 1%. The received macromodel is notable for its low order and high-fidelity output signals. Описано макромодель трифазного асинхронного двигуна, отриману для таких параметрів, як навантаження на валу, струм живлення однієї з фаз та частота обертання ротора. Експериментальні дані усереднено за період змінного струму живлення. Продемонстровано регуляризацію обчислення похідних вихідних сигналів макромоделі за допомогою згладжуючих кубічних сплайнів. Кількість коефіцієнтів макромоделі мінімізовано за методом редукції апроксимуючого поліному. Завдяки редукції ідентифікація макромоделі стала коректною. Адекватну поведінку макромоделі перевірено на сигналах, відмінних від сигналів, за якими збудовано макромодель. Експериментальні перехідні процеси відтворено двома нелінійними макромоделями першого порядку зі середньоквадратичною похибкою, меншою за 1 %. Отримана макромодель вирізняється гранично малим порядком і високою точністю відтворення вихідних сигналів.
Макромодель асинхронного двигуна за експериментальними даними
Keywords: mathematical macromodel; induction motor